Discovery of novel Tetrahydrobenzo[b]thiophene and pyrrole based scaffolds as potent and selective CB2 receptor ligands: the structural elements controlling binding affinity, selectivity and functionality - Osman, Noha; Ligresti, Alessia; Klein, Christian D.; Allarà, Marco; Rabbito, Alessandro; Di Marzo, Vincenzo; Abouzid, Khaled A.; Abadi, Ashraf H. (European journal of medicinal chemistry, 2016)
CB2-based therapeutics show strong potential in the treatment of diverse diseases such as inflammation, multiple sclerosis, pain, immune-related disorders, osteoporosis and cancer, without eliciting the typical neurobehavioral side effects of CB1 ligands. For this reason, research activities are currently directed towards the development of CB2 selective ligands. Herein, the synthesis of novel heterocyclic-based CB2 selective compounds is reported. A set of 2,5-dialkyl-1-phenyl-1H-pyrrole-3-carboxamides, 5-subtituted-2-(acylamino)/(2-sulphonylamino)-thiophene-3-carboxylates and 2-(acylamino)/(2-sulphonylamino)-tetrahydrobenzo[b]thiophene-3-carboxylates were synthesized. Biological results revealed compounds with remarkably high CB2 binding affinity and CB2/CB1 subtype selectivity. Compound 19a and 19b from the pyrrole series exhibited the highest CB2 receptor affinity (Ki = 7.59 and 6.15 nM, respectively), as well as the highest CB2/CB1 subtype selectivity (∼70 and ∼200-fold, respectively). In addition, compound 6b from the tetrahydrobenzo[b]thiophene series presented the most potent and selective CB2 ligand in this series (Ki = 2.15 nM and CB2 subtype selectivity of almost 500-fold over CB1). Compound 6b showed a full agonism, while compounds 19a and 19b acted as inverse agonists when tested in an adenylate cyclase assay. The present findings thus pave the way to the design and optimization of heterocyclic-based scaffolds with lipophilic carboxamide and/or retroamide substituent that can be exploited as potential CB2 receptor activity modulators.
Gesehen am 13.10.2020